The AHRC Landscape and Environment Programme Director’s Impact Fellowship - Veale, Lucy (University of British Columbia, Okanagan, 2014)
The Landscape and Environment programme was one of the first strategic research programmes to be launched by the Arts and Humanities Research Council (AHRC) soon after it acquired its royal charter in 2005. In 2010, programme Director Stephen Daniels was awarded an ‘Impact Fellowship’ to continue his Directorship of the programme for a further year (supported by a Coordinator and Research Fellow), with the aim of consolidating the work completed under the five year programme (2005-2010), focussing particularly on enhancing the transformative impact of programme research both on the research field and outside academia. This statement by the Research Fellow places the Impact Fellowship within the context of the growing research impact agenda, before reviewing the activities of the project which used research on landscape and environment as a framework for demonstrating the value and impact of arts and humanities research more widely. The opportunities and challenges provided by the Impact Fellowship and other funding initiatives of its type, for both academics and external partner organisations are also explored.